Application of good faith as necessary limits in exercising the termination for convenience clause [electronic resource] - Nik Abdul Hafiz Nik Abdullah, 1977- author 585327; Rosli Abdul Rashid, supervisor 408804; Fakulti Alam Bina 8041 (2015)
Thesis (Sarjana Sains (Pengurusan Kontrak Pembinaan)) - Universiti Teknologi Malaysia, 2015